Distributed Ledger Technology in Financial Markets. The European Union Experiment - Jiménez-Gómez, Briseida Sofía (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The European Union Regulation 2022/858 of 30 May 2022 establishes a pilot regime for market infrastructures based on distributed ledger technology. The Pilot Regulation is part of the 2020 Digital Finance Strategy whose objective is for the European Union to embrace the digital revolution and to benefit consumers and business. This article analyses the reasons of this new regulatory option and why this represents a different paradigm of legislation, considering first some advantages, risks and challenges that applying distributed ledger technology in financial markets can encounter. Moreover, this article examines the content of the EU Pilot Regulation with a critical perspective, comparing the previous proposal of Regulation with the current Pilot Regulation which enters into force mainly in March 2023. Significance of this Pilot Regulation could be enhanced if it coordinates with other policy goals such as sustainability and transparency set by the EU legislator. Lacking that coordination, this Pilot Regulation could be perceived as a miss opportunity to foster a digital and green financial markets transition.
Keywords: Pilot Regulation; Market infrastructures; Capital Markets; European Law; Distributed Ledger Technology